Design and Fabrication of Temperature‐Sensitive Nanogels with Controlled Drug Release Properties for Enhanced Photothermal Sterilization. Issue 72 (27th September 2017) - Li, Luoyuan; Fu, Limin; Ai, Xicheng; Zhang, Jianping; Zhou, Jing
Abstract: For better removal of excessive free radicals and harmful bacteria from the human body, the development of synergistic antioxidant and antibacterial agents is urgently required. Herein, we designed novel temperature‐sensitive, curcumin (Cur)‐loaded nanogels for the application of scavenging reactive oxygen species and killing pathogenic bacteria. Photothermal sterilization, different from traditional antibiotics, is a promising and effective treatment for pathogenic bacterial infection. The nanogels were fabricated by using poly( N ‐isopropylacrylamide) (a temperature‐sensitive hydrogel) to encapsulate poly(3, 4‐ethylenedioxythiophene) nanoparticles (photothermal agents) and Cur through a reformative precipitation polymerization. When triggered by near‐IR light, the Cur‐loaded nanogels exhibited high (56.8 %), and excellent temperature‐sensitive effects. Moreover, the light‐induced temperature increase can also weaken the interaction between the networks of PNIPAAm and Cur, to show excellent antioxidant and antibacterial performance (90 % cell death) of the nanogels. Abstract : Bacteria‐killing polymer nanogels : Novel temperature‐sensitive PEDOT@PNIPAAm nanogels loaded with curcumin were fabricated, showing high, excellent controlled drug release properties, as well as antioxidant and antibacterial activities.